2021
DOI: 10.1007/s12028-020-01161-5
|View full text |Cite
|
Sign up to set email alerts
|

Andexanet Alfa Versus 4-Factor Prothrombin Complex Concentrate for Reversal of Factor Xa Inhibitors in Intracranial Hemorrhage

Abstract: Background/Objective: There are limited data on the risks and benefits of using andexanet alfa (AA) in comparison with four-factor prothrombin complex concentrate (4F-PCC) to reverse factor Xa inhibitors (FXi) associated intracranial hemorrhage (ICH). We sought to describe our experience with AA or 4F-PCC in patients with oral FXi-related traumatic and spontaneous ICH. Methods:We conducted a retrospective review of consecutive adult patients with FXi-related ICH who received AA or 4F-PCC. FXi-related ICH cases… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 19 publications
1
61
0
2
Order By: Relevance
“…5,29,30 Irrespective of these recommendations there is currently limited evidence comparing the 2 agents. 15,[31][32][33] Therefore, the aim of this retrospective cohort is to compare hemostatic efficacy and safety outcomes between andexanet alfa and 4F-PCC for reversal of FXa-inhibitor-related bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…5,29,30 Irrespective of these recommendations there is currently limited evidence comparing the 2 agents. 15,[31][32][33] Therefore, the aim of this retrospective cohort is to compare hemostatic efficacy and safety outcomes between andexanet alfa and 4F-PCC for reversal of FXa-inhibitor-related bleeding.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the overall mortality rate in a recent 4F-PCC meta-analysis in FXa inhibitor bleeding was 18% compared to 12.13% in our analysis and 14% in the ANNEXA-4 trial [ 27 ]. The studies done by Ammar et al and Barra et al showed a higher mortality rate of 39% and 22% respectively which is higher than that of other studies as these studies included only ICH patients [ 17 , 18 ]. Mortality was also significant in a study done by Culbreth (40%) as 14 out of 15 patients had ICH.…”
Section: Reviewmentioning
confidence: 79%
“…Only the Connolly et al study had more incidence of stroke (14) than DVT (13) [ 21 ]. Ammar et al reported no thrombotic event in the 4F-PCC group, while one event was reported in the Barra et al study, which is fewer than that reported in the AA group [ 17 , 18 ]. Restarting anticoagulation showed a significant decrease of thrombotic events in studies by Connolly et al and Stevens et al [ 21 , 26 ].…”
Section: Reviewmentioning
confidence: 97%
See 1 more Smart Citation
“…Low-dose 4F-PCC was successfully used to manage DOAC-associated ICH in 94.7% of treated patients [ 66 ]. A retrospective analysis of adult patients with FXa inhibitor-related ICH receiving andexanet alfa or 4F-PCC reported no difference in functional outcome or thrombotic events between the two groups [ 67 ]. In another retrospective study of FXa-associated ICH, excellent or good haemostatic efficacy was observed in 16/18 (89%) patients treated with andexanet alfa, compared with 6/10 (60%) patients treated with 4F-PCC [ 68 ].…”
Section: Bleeding In Patients On Oral Anticoagulantsmentioning
confidence: 99%